Metal Complexes of Schiff Bases Prepared from Quinoline-3-Carbohydrazide with 2-Nitrobenzaldehyde, 2-Chlorobenzaldehyde and 2,4-Dihydroxybenzaldehyde: Structure and Biological Activity - Mahmoud Sunjuk; Lana Al-Najjar; Majed Shtaiwi; Bassam I. El-Eswed; Kamal Sweidan; Paul V Bernhardt; Hiba Zalloum; Luay Al-Essa (Inorganics, 2023)
Three Schiff base ligands, NQ, CQ and HQ, were prepared from the reaction of quinoline-3-carbohydrazide with 2-nitrobenzaldehyde, 2-chlorobenzaldehyde and 2,4-dihydroxybenzaldehyde, respectively, and were investigated for their coordination to Cu (II), Ni(II), Co(II), Cd(II), Cr(III) and Fe(III) chlorides. The NQ preparation and the X-ray structure of NQ and CQ, as well as the transition metal complexes of NQ, CQ and HQ, were reported for the first time. FTIR, 1H-NMR, magnetic susceptibility and elemental analysis were used to study the coordination of ligands to the metal ions. Based on the magnetic susceptibility and elemental analysis results, octahedral structures of the complexes such as [CuL2Cl(OH)], [FeL2Cl2(OH)] and [CoL2Cl(OH)] were proposed for L = NQ, CQ and HQ. The relatively large Cd(II) exhibited [CdL3(OH)2]. The FTIR study revealed that NQ and CQ are coordinated to the metal ions via azomethine nitrogen and carbonyl oxygen while HQ through azomethine nitrogen and phenolic oxygen. Despite the high solvation power of DMSO solvent in 1H-NMR experiments, the azomethine HC=N peak at 9.3 ppm is the most affected by complexation with metal ions. On the other hand, quinoline nitrogen seems to be a weaker coordinating site than the azomethine nitrogen. The HQ ligand, containing phenolic groups, and its complexes with Cu and Ni were found to have inhibitory effects on human breast adenocarcinoma MCF-7 and human chronic myelogenous leukemia K562. Nevertheless, metal ions did not exhibit a significant synergistic effect on the antiproliferative activity of the ligands investigated.